Modernizations In Interdisciplinary Teams: Connecting Technology For Enhanced Collaboration Between Social Workers And Nurses. An Update (Journal of Namibian Studies : History Politics Culture, 2022)
This paper explores the role of technological innovations in enhancing collaboration between social workers and nurses in healthcare settings. With the increasing complexity of patient needs and the growing importance of interdisciplinary teamwork, leveraging technology has become essential for effective communication, coordination, and decision-making. Telehealth solutions, electronic health records (EHR) systems, mobile applications for care coordination, remote monitoring devices, and artificial intelligence (AI) tools are among the key technologies transforming collaborative practice. By harnessing these innovations, social workers and nurses can overcome geographical barriers, access real-time patient information, streamline care coordination, and make data-driven decisions to improve patient outcomes. This paper highlights the potential benefits of technological integration in facilitating seamless collaboration between social workers and nurses, ultimately enhancing the delivery of patient-centered care.